2011
DOI: 10.1017/s1461145711000976
|View full text |Cite
|
Sign up to set email alerts
|

The effect of clozapine on the AMPK-ACC-CPT1 pathway in the rat frontal cortex

Abstract: Clozapine is an antipsychotic drug that has a greater efficacy than other medications in some contexts, especially for the treatment of treatment-resistant schizophrenia. However, clozapine induces more metabolic side-effects involving abnormality in lipid metabolism compared to other antipsychotics. AMP-activated protein kinase (AMPK) plays a central role in controlling lipid metabolism through modulating the downstream acetyl CoA carboxylase (ACC) and carnitine palmitoyl transferase 1 (CPT1) pathway. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
34
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 58 publications
5
34
1
1
Order By: Relevance
“…These results demonstrated a novel mechanism by which LBP exerts a powerful lipid-lowering effect by activating the SIRT1/AMPK pathway and reducing lipid synthesis. Moreover, other researchers have shown that activation of ACC leads to increased intracellular malonyl-CoA, which blocks CPT-1α expression and abrogates fatty acid β-oxidation32. Surprisingly, LBP strongly upregulated CPT-1α expression and boosted fatty acid β-oxidation by repressing intracellular malonyl-CoA accumulation (Figs 4G–I and 5E–G).…”
Section: Discussionmentioning
confidence: 73%
“…These results demonstrated a novel mechanism by which LBP exerts a powerful lipid-lowering effect by activating the SIRT1/AMPK pathway and reducing lipid synthesis. Moreover, other researchers have shown that activation of ACC leads to increased intracellular malonyl-CoA, which blocks CPT-1α expression and abrogates fatty acid β-oxidation32. Surprisingly, LBP strongly upregulated CPT-1α expression and boosted fatty acid β-oxidation by repressing intracellular malonyl-CoA accumulation (Figs 4G–I and 5E–G).…”
Section: Discussionmentioning
confidence: 73%
“…PPARα agonist up-regulates the expression of CPT1 [42] and inhibits TNF-α and IL-6 levels [43,44]. AMPK activation increases fatty acid oxidation likely by activating PPARα [45] and CPT1 [46]. Therefore, AMPK and PPARα are two critical regulators of hepatic lipid metabolism and may be therapeutic targets in the treatment of NAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…However, a study in rats has reported that a single intraperitoneal injection of clozapine (5-20mg/kg) significantly activated AMPK-CPT1 signaling in the prefrontal cortex, suggesting that clozapine affects lipid metabolism in the brain. [87] In addition to the hypothalamus, H1 receptors and AMPK-CPT1 signaling in the nucleus of solitary tract (NTS) in the brainstem may also play a role in feeding regulation and contribute to SGA-induced weight gain. Previous studies in rats found that the brainstem dorsal vagal complex (DVC) is significantly involved in mediating olanzapine-induced weight gain.…”
Section: Intracellular Mechanisms For Sga-induced Weight Gain Associamentioning
confidence: 99%